Teaching Tolerance in the Foreign Language Classroom: A Personal Reflection - Luna, Boni (Learning languages, 1997)
Presents a personal reflection of the difficulties of being a non-English-speaking child in the United States. As a Spanish-language instructor, the author realizes the potential she has to influence her students, teaching not just about the language but also about the culture of Spanish-speaking people. (ER)